Hematologic and clinical chemistry reference intervals for six species of wild birds frequently rescued in the Republic of Korea - Kim, Myeongsu; Wut Hmohn, Zun Zun; Jang, Woochan; Baek, Geonwoo; Han, Jae-Ik (Frontiers in Veterinary Science, 2025)
ObjectiveReference intervals for hematologic and clinical chemistry values are useful when diagnosing a pathologic condition in animals. This study establishes relevant reference intervals for six species of wild birds that are frequently rescued at wildlife rescue centers in the Republic of Korea.MethodsForty-two Eurasian eagle owls (Bubo bubo), 34 Oriental turtle doves (Streptopelia orientalis), 73 domestic pigeons (Columba livia domestica), 27 brown hawk-owls (Ninox scutulata), 76 common kestrels (Falco tinnunculus), and 25 Eurasian magpies (Pica pica) were included in this study. Only released birds were included because they were judged to be clinically healthy through physical examinations, blood examinations, radiographic examinations, and flight evaluations. The reference intervals were set according to the American Society for Veterinary Clinical Pathology guideline, and if there were fewer than 20 birds, the reference intervals were set between the 2.5th percentile and the 97.5th percentile. One-way ANOVA was performed to compare hematologic and clinical chemistry parameters among species.ResultsThe total protein levels in carnivorous birds (Eurasian eagle owl, brown hawk-owl, and common kestrel) were significantly higher than those in omnivorous birds (Oriental turtle dove and domestic pigeon). The common kestrel exhibited significantly lower white blood cell counts and heterophil counts than other species. The Eurasian magpie had significantly higher eosinophils than other species.ConclusionThis study provides reference intervals for wild birds often rescued at wildlife rescue centers in Korea. It is expected that these reference intervals will be used as important data in diagnosing diseases in rescued wild birds.